Looking for the Genes Related to Lung Cancer From Nasal Epithelial Cells by Network and Pathway Analysis - Qureshi, Noman; Chi, Jincheng; Qian, Yanan; Huang, Qianwen; Duan, Shaoyin (Frontiers in Genetics, 2022)
Previous studies have indicated that the airway epitthelia of lung cancer-associated injury can extend to nose and its are with abnormal gene expression. This study is to find the lung cancer-related genes from the nosal epitthelia as the bio-markers for lung cancer detection. WGCNA were performed to calculate the module-trait correlations of lung cancer based on the public microarray dataset and their data were processed by statistics of RMA and T test. Four specific modules associated with clinical features of lung cancer were constructed, including the blue, brown, yellow and light blue. Of which blue or brown modules showed strong connection of genetic connectivity. From brown module, the HCK, NCF1, TLR8, EMR3, CSF2RB and DYSF are the hub genes, and from blue modules, SPEF2, ANKFN1, HYDIN, DNAH5, C12orf55 and CCDC113 are the pivotal genes corresponding to grade. These genes can be taken as the bio-makers to develop a noninvasive method of diagnosing early lung cancer.